Mechanochemical Synthesis of Free-Standing Platinum Nanosheets and Their Electrocatalytic Properties - Rana, M. (WILEY-VCH Verlag GmbH, 2015)
Robust, 26 nm thick free-standing platinum nanosheets, an extremely rare morphology for metal nanostructures, are obtained by employing fluid induced shearing force of the order of 1.8 N and differential shear-stress of 0.5 kPa across the diameter of a Te template nanorod undergoing galvanic displacement by Pt4+. Corrugation leads to their large surface area and much improved electrocatalytic properties when compared with conventional Pt catalysts.
Only IISERM authors are available in the record.
Keywords: electrocatalysis; galvanic displacements; mechanochemical synthesis; metal nanosheets